GASTRO INTESTINAL PARASITIC INFECTIONS IN A DESI FOWL (Gallus gallus domesticus) OF CHENNAI, TAMIL NADU- A CASE REPORT - K.T. Kavitha; B. Rubinibala; S. Ramesh; Bhaskaran Ravi Latha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Mixed infections with four gastrointestinal parasites were recorded in a desi fowl presented for post mortem in Chennai. The morphological characters of the worms found in the lumen of the gizzard, duodenum and caecum of a desi fowl were studied and the worms were identified as Ascaridia galli and Heterakis gallinarum. The caecum of a bird showed pathological changes including congestion and haemorrhages. Examination of the intestinal contents revealed the presence of eggs of A. galli and Capillaria spp along with oocyst of Eimeria spp.